2018
DOI: 10.1038/s41396-018-0222-x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple stable states in microbial communities explained by the stable marriage problem

Abstract: Experimental studies of microbial communities routinely reveal that they have multiple stable states. While each of these states is generally resilient, certain perturbations such as antibiotics, probiotics, and diet shifts, result in transitions to other states. Can we reliably both predict such stable states as well as direct and control transitions between them? Here we present a new conceptual model-inspired by the stable marriage problem in game theory and economics-in which microbial communities naturall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 70 publications
1
69
0
Order By: Relevance
“…Analyzing both theoretically and experimentally a minimal bistable community, we have shown that feedback between microbial 30 growth and environmental conditions (specifically, the pH) can mechanistically drive these transitions. While our results enhance the relevance of environmentally mediated interactions [46]-[49] in the microbial world, phenomenological models such as the generalized Lotka-Volterra model [50] and the stable marriage problem [51] indicate that analogous community dynamics could unfold from different microbial interactions. Analogous boom-and-bust invasions [52] have 35 also been reported as a main cause of macroecosystem disruption.…”
Section: Discussionsupporting
confidence: 55%
“…Analyzing both theoretically and experimentally a minimal bistable community, we have shown that feedback between microbial 30 growth and environmental conditions (specifically, the pH) can mechanistically drive these transitions. While our results enhance the relevance of environmentally mediated interactions [46]-[49] in the microbial world, phenomenological models such as the generalized Lotka-Volterra model [50] and the stable marriage problem [51] indicate that analogous community dynamics could unfold from different microbial interactions. Analogous boom-and-bust invasions [52] have 35 also been reported as a main cause of macroecosystem disruption.…”
Section: Discussionsupporting
confidence: 55%
“…It is usually understood as the result of transparently cooperative processes, such as production of a public good [32], and modeled via an explicit cooperative term. In resourcecompetition models, multistability has been observed when species consume nutrients one at a time [33] or with unequal stoichiometries [34]. Here, both the Allee effect and multistability emerge naturally from the ability of a population to render its resource environment more favorable to itself.…”
Section: Discussionmentioning
confidence: 99%
“…(2) for a review), which have been previously modelled 92 in the context of competition for nutrients (5,4) and without phages. In order for a 93 phage-bacterial ecosystem to be in principle capable of bistability, the slow-growing 94 bacterial species needs to produce disproportionately more phages per each unit 95 of consumed nutrient than the fast-growing one:…”
Section: Conditions For Bistability and Regime Shiftsmentioning
confidence: 99%
“…In microbial ecosystems (2) these 41 ms Submission Template mSystems Submission Template mSystems Submission Template mSystems Submission Template mSystems Submission Template mSystems Submission Tem transitions are known to be possible when a bacterial species directly produces some 42 metabolic waste products or antibiotics (3) that inhibit the growth of other bacteria. 43 They may also occur when bacterial species compete for several food sources, which 44 they use either in different stoichiometric ratios (4) or in different preferential orders 45 (5). Here we explore a new type of regime shifts caused by interactions between 46 bacteria and phages.…”
Section: Introductionmentioning
confidence: 99%